Effects of long term use of organic and inorganic fertilizers on soil fertility and productivity under paddy- sesame cropping system - Gaddi, Ashok Kumar; Basavanneppa, MA; Tevari, Prabhuling (Bangladesh Journal of Botany, 2020)
A field study was conducted to analyze the effect of long term use of organic and inorganic fertilizers on productivity and soil fertility under paddy-sesame cropping system. Application of 100% NPK + secondary and micro-nutrients based on soil test (T7) showed significantly higher mean grain yield of paddy (4735 kg/ha) and sesame (460 kg/ha) and rice equivalent yield (5348 kg/ha) followed by application of 50% NPK + 50% N as Farmyard manure (FYM) + inorganic source of micronutrients as per soil test (T1). Whereas, application of 50% recommended dose of nitrogen (RDN) through FYM + bio-fertilizers for N + Recommended dose of phosphorus (RDP) through rock phosphate + phosphorus solubalizing bacteria (PSB) showed significantly least mean grain yield of paddy (3209 kg/ha) and sesame (314 kg/ha) and rice equivalent yield (3628 kg/ha). Further, among organic treatments (T2 to T6), higher mean grain yield of paddy (3834 kg/ha), sesame (326 kg/ha) and rice equivalent yield (4269 kg/ha) as compared to other treatments was recorded following the application of one third of RDN through FYM + one third of RDN through vermicompost + one third of RDN through neem cake + bio-fertilizers containing N and P carriers (T6). Whereas, higher nutrient status with respect to major and micronutrients and the improved soil fertility status was recorded in organic treatment plots. The application of nutrients through organic sources would improve the soil fertility status under paddy-sesame cropping system.